Precipitating factors in patients with spontaneous coronary artery dissection: Clinical, laboratoristic and prognostic implications - Gurgoglione, Filippo Luca; Rizzello, Davide; Giacalone, Rossella; Ferretti, Marco; Vezzani, Antonella; Pfleiderer, Bettina; Pelà, Giovanna; De Panfilis, Chiara; Cattabiani, Maria Alberta; Benatti, Giorgio; Tadonio, Iacopo; Grassi, Francesca; et al. (International journal of cardiology, 2023)
Spontaneous coronary artery dissection (SCAD) often presents with acute coronary syndrome and underlying pathophysiology involves the interplay between predisposing factors and precipitating stressors, such as emotional and physical triggers. In our study we sought to compare clinical, angiographic and prognostic features in a cohort of patients with SCAD according to the presence and type of precipitating stressors. Consecutive patients with angiographic evidence of SCAD were divided into three groups: patients with emotional stressors, patients with physical stressors and those without any stressor. Clinical, laboratoristic and angiographic features were collected for each patient. The incidence of major adverse cardiovascular events, recurrent SCAD and recurrent angina was assessed at follow-up. Among the total population (64 subjects), 41 [64.0%] patients presented with precipitating stressors, including emotional triggers (31 [48.4%] subjects) and physical efforts (10 [15.6%] subjects). As compared with the other groups, patients with emotional triggers were more frequently female (p = 0.009), had a lower prevalence of hypertension (p = 0.039] and dyslipidemia (p = 0.039), were more likely to suffer from chronic stress (p = 0.022) and presented with higher levels of C-reactive protein (p = 0.037) and circulating eosinophils cells (p = 0.012). At a median follow-up of 21 [7; 44] months, patients with emotional stressors experienced higher prevalence of recurrent angina (p = 0.025), as compared to the other groups. Our study shows that emotional stressors leading to SCAD may identify a SCAD subtype with specific features and a trend towards a worse clinical outcome. •Emotional stressors are the predominant stressor type in SCAD.•Emotional stressors may identify a SCAD subtype with specific features and a worse outcome.•Emotional stressors leading to SCAD are associated with chronic stress and inflammatory state.•Patients with emotional stressors experience higher rates of recurrent angina at follow-up.